2017
DOI: 10.3389/fpls.2017.01517
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Critical Nitrogen Dilution Curve Based on Leaf Area Duration in Wheat

Abstract: Precise quantification of plant nitrogen (N) nutrition status is essential for crop N management. The concept of critical N concentration (Nc) has been widely used for assessment of plant N status. This study aimed to develop a new winter wheat Nc dilution curve based on leaf area duration (LAD). Four field experiments were performed on different cultivars with different N fertilization modes in the Yangtze River basin and Yellow River basin in China. Results showed that the increase in LAD with increasing cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Further, the strong correlation between biomass and Δ 13 C ( Table 2 ) indicates the association between residuals and biomass ( Figure 6A ) was likely mediated by the effect of water deficit on biomass. Our dilution curve thus returned lower critical nitrogen compared with the original curve for well-watered wheat in France ( Justes et al, 1994 ). Dilution curves for winter wheat in China ( Yin et al, 2018 ) and for spring wheat in Canada ( Ziadi et al, 2010 ) were also below the original curve for well-watered crops, and this is partially attributable to water deficit.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Further, the strong correlation between biomass and Δ 13 C ( Table 2 ) indicates the association between residuals and biomass ( Figure 6A ) was likely mediated by the effect of water deficit on biomass. Our dilution curve thus returned lower critical nitrogen compared with the original curve for well-watered wheat in France ( Justes et al, 1994 ). Dilution curves for winter wheat in China ( Yin et al, 2018 ) and for spring wheat in Canada ( Ziadi et al, 2010 ) were also below the original curve for well-watered crops, and this is partially attributable to water deficit.…”
Section: Discussionmentioning
confidence: 55%
“…We examined the combined effects of water stress, phenology, partitioning of biomass among organs, and partitioning between structural and WSC on the critical nitrogen concentration of wheat crops. Tight nitrogen dilution curves are often derived for well-watered crops, e.g., wheat ( Justes et al, 1994 ) and maize ( Plénet and Lemaire, 1999 ); larger scatter was observed in potato crops under variable water supply ( Bélanger et al, 2001 ). Here we found scattered dilution curves for crops grown under varying water deficits ( Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of the a parameter has been reported in other studies, where the value estimated for winter wheat in eastern China was 3.06, adjusted to a leaf DM production between .52 and 2.64 t DM ha –1 (Yao et al., 2014); a value of 2.85 in winter wheat was also projected when the curve was adjusted to spike DM production between .75 and 7.23 t DM ha –1 (Zhao et al., 2016). In addition to the use of alternative adjustments of the dilution curve proposed by different authors for the crop of wheat, such as a function of leaf DM (Yao et al., 2014), spike DM (Zhao, 2014) and area foliar duration (Wang et al., 2017), it has been shown that the effect of water stress changes the C allocation during biomass production in wheat crop (Hoogmoed & Sadras, 2016). This water stress results in lower critical concentrations of N and increased water‐soluble carbohydrates in the crop, due to the genotype, the environment and their interaction under conditions of water deficit (Hoogmoed & Sadras, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The critical nitrogen concentration (N c ) used to determine the dilution curve based on shoot biomass production have been successfully applied in diverse crops species (Chakwizira, de Ruiter, Maley, & Teixeira, 2016; Gastal et al., 2015; Gόmez, Magnitskiy, & Rodriguez, 2019; Zhao, 2014). However, recent studies have shown that these curves must be adjusted for different environments (Hoogmoed & Sadras, 2016), agronomic management systems (Reyes et al., 2015), organ specific dry matter contents (Zhao et al., 2016), leaf area durations (Wang et al., 2017), and water stress in crops (Hoogmoed & Sadras, 2018).…”
Section: Introductionmentioning
confidence: 99%